2013
DOI: 10.3109/07357907.2013.789904
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Patterns of Use of Gemcitabine for Metastatic Pancreatic Cancer: A Population-Based Study

Abstract: Gemcitabine was approved for advanced pancreatic cancer in 1996. We investigated uptake and predictors of its use. We identified 3,231 individuals > 65 years in the SEER-Medicare database with stage IV pancreatic adenocarcinoma, diagnosed between 1998-2005, who survived > 30 days. Of these, 54% received chemotherapy, 93% with gemcitabine. Gemcitabine nonreceipt was associated with advanced age and unmarried (OR: 0.65, 95% CI: 0.55-0.76). Diagnosis in 2004-2005 versus 1998-2000 was more likely to receive gemcit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…Most previous observational studies only included patients with microscopically confirmed pancreatic cancer [5,11,13,21,22,32]. Although pathologic confirmation of pancreatic cancer prior to chemotherapy is strongly recommended [27,33], one in ten of treated patients in our study started chemotherapy without prior microscopic tumor verification.…”
Section: Discussionmentioning
confidence: 93%
“…Most previous observational studies only included patients with microscopically confirmed pancreatic cancer [5,11,13,21,22,32]. Although pathologic confirmation of pancreatic cancer prior to chemotherapy is strongly recommended [27,33], one in ten of treated patients in our study started chemotherapy without prior microscopic tumor verification.…”
Section: Discussionmentioning
confidence: 93%
“…One possible explanation for that finding is the cumulative effect of gradual increases in chemotherapy uptake in the palliative setting 29 . Use of recently developed chemotherapy regimens such as folfirinox (approved in Ontario in 2011) continues to increase for pcc patients 30 , and survival for individuals diagnosed after 2011 is expected to reflect the effect of those regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, elderly patients remain poorly represented in clinical trials 5 and are often not recommended for standard therapy. 6,7 Hutchins et al demonstrated that patients 65 years or older were significantly underrep-resented in the Southwest Oncology Group treatment trials, which included trials specifically for pancreas cancer. 5 In another study, 11% of physicians explicitly reported that age was a reason for not enrolling elderly patients in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…8 In terms of standard therapy, Oberstein et al investigated the Surveillance, Epidemiology, and End Results-Medicare database for patients with metastatic pancreas adenocarcinoma diagnosed between 1998 and 2005 and demonstrated that the likelihood of receipt of palliative gemcitabine decreased with advancing age. 7 Additionally, Vijayvergia et al also reported differences in patterns of care and outcomes of elderly versus younger patients with metastatic pancreatic cancer. Specifically, the authors showed at their institution that older patients (> 65 years of age) despite having similar performance status and disease characteristics were less likely to receive any chemotherapy and if treated were less likely to receive more than 1 chemotherapy agent.…”
Section: Introductionmentioning
confidence: 99%